Analisis Kesiapan Diri Mahasiswa Pendidikan Teknik Elektro melaksanakan Praktek Lapangan Kependidikan - Zul Fitra; Habibullah Habibullah (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
Abstract— This study aims to determine how the level of self-readiness in teaching to students of Electrical Engineering Education Program 2017 when implementing educational field practice at the State University of Padang (UNP). This type of research is descriptive research. The intended research subjects were students of Electrical Engineering Education Class of 2017, data collection was carried out using questionnaires or questionnaires using likert scale, while the tests carried out include validity tests, reliability tests and data analysis used are descriptive statistical techniques using mean values, standard deviation values and to determine how large the data distribution using Score categories 1 to 5. The results showed that self-readiness in teaching to students of Electrical Engineering Education 2017 UNP has a different level of category in each indicator, the category is contained in the core activities in teaching as many as 18 students agreed in the core activities of teaching can melaksanakanya well, preliminary teaching activities are in the low category can be seen as many as 18 students agreed in the preliminary teaching activities have not been able to carry it out properly and the closing teaching activities are in the low category as many as 17 students belong to this category. It can be concluded that the self-readiness in teaching experienced by students during the educational field practice is different for each individual to carry out the perfect educational field practice is the desired achievement and expectations of every student, if the self-readiness in teaching is high, it will realize the effective and perfect educational field practice.